2019
DOI: 10.1111/rsp3.12242
|View full text |Cite
|
Sign up to set email alerts
|

European identity and citizens' support for the EU: Testing the utilitarian approach

Abstract: Despite Cohesion Policy representing one‐third of the EU budget, research on the role of EU Cohesion Policy in promoting the European identity is still scarce. Taking stock of a new dataset of citizens' support for and identification with the EU identity at the regional level, we aim to answer to the following questions: what are the determinants of support and identification with EU? Do EU fiscal transfers affect public support for the EU and the European identity? Do citizens' awareness about the Cohesion Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 35 publications
(61 reference statements)
1
18
0
Order By: Relevance
“…In both regions studied these two factors made building awareness of Cohesion Policy among the citizens more difficult and hence limited the scope for boosting positive EU identification among the citizens. This confirms the expectation from previous research that awareness of EU Cohesion Policy is crucial for it having any effect on the citizen's views on the EU (Aiello, Reverberi, and Brasili 2019;Capello and Perucca 2019;Osterloh 2011). But also this contributes to the understanding of the Cohesion Policy -EU identification nexus by highlighting that communication and implementation 'architecture' matter.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In both regions studied these two factors made building awareness of Cohesion Policy among the citizens more difficult and hence limited the scope for boosting positive EU identification among the citizens. This confirms the expectation from previous research that awareness of EU Cohesion Policy is crucial for it having any effect on the citizen's views on the EU (Aiello, Reverberi, and Brasili 2019;Capello and Perucca 2019;Osterloh 2011). But also this contributes to the understanding of the Cohesion Policy -EU identification nexus by highlighting that communication and implementation 'architecture' matter.…”
Section: Discussionsupporting
confidence: 89%
“…Last but not least, we confirmed that the scale of funding also matters. Even though previous research suggested that the relationship between magnitude of funding and support for the EU is not straightforward (see Aiello, Reverberi, and Brasili 2019;Capello and Perucca 2019;Dąbrowski, Stead, and Mashhoodi 2019;Smętkowski and Dąbrowski 2019), the evidence from from stakeholder interviews and focus groups conducted, does suggest that the relatively small allocation of funding to the Dutch regions is hardly noticeable and can only have a limited impact on for positive EU identification. One of its anticipated effects of Cohesion Policy is to foster greater citizen attachment to the EU.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Aiello, Brasili, and Reverberi () focus on citizens' awareness and perceptions of EU regional policy as determinants of EU support. The analysis shows a predominance of the perceived elements on the objective ones as determinants of trust in EU institutions.…”
Section: Structure Of the Special Issuementioning
confidence: 99%
“…Taken together, the results from these studies support the general messages and policy implications discussed in the previous section. Cohesion Policy could be a powerful tool for promoting European identity, if the target of reduction of inequality within the EU is achieved (Aiello et al, ; Capello & Perucca, ; Dąbrowski et al, ). At the same time, however, this is likely to happen only if effective strategies of information, communication and involvement will be developed and implemented (Brasili et al, ; López‐Bazo & Royuela, ; Smętkowski & Dąbrowski, ).…”
Section: Structure Of the Special Issuementioning
confidence: 99%